Isolation, characterization, and proof of concept evaluation of serially adapted bacteriophages against multidrug-resistant Escherichia coli - Varun Rathi; Prakash R. Nayak; Namdeo R. Bulbule; Milind M. Chawak; Atharva Poundarik (Folia Microbiologica, 2026)

Updated Recommendations for the Bioanalysis of Antibody–Drug Conjugates (ADC) from the ADC working group of the AAPS Bioanalytical Community - Jim X. Shen; Robert Dodge; Shoshana Oberstein; Jennifer Cunliffe; Varun Ramani; Soumya Mohana Sundaram; Ines C. Santos; Chongwoo Yu; Sanjay L. Dholakiya; Seema Kumar; Xiaohui Sophia Xu; Sasha Fraser; et al. (The AAPS Journal, 2026)
Antibody–drug conjugates (ADCs) represent a rapidly evolving therapeutic modality, combining the selective targeting of monoclonal antibodies with highly potent small molecule payloads. Their inherent structural complexity demands a sophisticated and multi-faceted bioanalytical approach spanning preclinical discovery through late-stage clinical development. This white paper, developed by the ADC Working Group of the AAPS bioanalytical community, comprising over 100 members from industry, contract research organizations (CROs), and regulatory agencies, provides updated recommendations for ADC bioanalysis. Building upon the foundational 2013 AAPS position paper and recent publications governing regulatory frameworks on PK considerations, this work addresses advances in bioanalytical quantitation strategies for total antibody (tAb), conjugated ADC, free (unconjugated) payload, and drug-to antibody ratio (DAR); novel immunogenicity assessment considerations; soluble target interference; critical reagent lifecycle management; payload-specific stability requirements; cross-validation strategies; and regulatory considerations. The recommendations presented herein reflect over a decade of scientific progress and are designed to serve as a comprehensive, empirically validated, and industry aligned bioanalytical framework for contemporary ADC drug development.